Functional outcomes of medical and trauma patients in a critical care unit using the Chelsea Critical Care Physical Assessment tool - Mshunqane, Nombeko (University of Pretoria, 2024)
Dissertation (MSc (Physiotherapy))--University of Pretoria, 2024.